Detection of hdc Gene from Histamine Producing Bacillus subtillis and Serratia marcescens - Laxmi, C. Aishwarya; Munaliga, S.; Babu, N.G. Ramesh; Ragunathan, R. (International Journal of Applied Sciences and Biotechnology, 2017)
In the present study, two histamine producing bacteria were used to detect the presence of hdc gene using PCR. The histamine production was confirmed by using Soyabean Casein Digest Agar (Tryptone Soya Agar). The DNA was isolated using Phenol: chloroform method. PCR was carried out using hdc gene and the amplified product was confirmed (657bps and 668 bps respectively). Further, the DNA and the PCR product were transformed into E.coli and the gene transformation was confirmed. Int. J. Appl. Sci. Biotechnol. Vol 5(3): 309-312